Histopathological effect of balloon dilation in a live rabbit: Implications for the pediatric airway. (7th July 2015) - Modi, Vikash K.; Visaya, Jiovani M.; Ward, Robert F.
Abstract : Objective/Hypothesis: To examine the short‐ and long‐term histopathologic changes that occur in the subglottis in response to airway balloon dilation (ABD) with different balloon diameters and inflation pressures. Study Design: Prospective animal study using forty‐two 8‐month old New Zealand white rabbits at an academic animal research facility. Methods: Thirty‐nine live New Zealand rabbits underwent a single ABD with diameters ranging from 6.0 mm to 10.0 mm and with pressures between 5.0 atmospheres (atm) to 15.0 atm. Animals were euthanized on postoperative days (POD) 1, 7, and 30, and the histopathological changes of the subglottis were examined. Three rabbits served as controls and underwent no ABD. Results: The subglottic airway diameter of all specimens measured 5.4 mm. When examining the fracture rate by balloon diameter, we found the following: 0 of 6 (0%) at 6 mm, 0 of 9 (0%) at 7 mm, 6 of 9 (67%) at 8 mm, 8 of 9 (89%) at 9 mm, and 6 of 6 (100%) at 10 mm. There was a statistically significant relationship with the rate of cricoid fracture as balloon diameter increased ( P < .0001). All fractures occurred at the anterior cricoid lamina. On POD 1, we found mild ulceration in 5 of 6 (83%) using a 6‐mm or 7‐mm balloon and in 0 of 6 (0%) using an 8‐mm, 9‐mm, or 10‐mm balloon; and moderate/severe ulceration in 1 of 6 (16.67%) using a 6‐mm or 7‐mm balloon and in 11 of 11 (100%) using an 8‐mm, 9‐mm, or 10‐mm balloon ( P < .0001). Also on POD 1, we found mild edema in 6 of 6 (100%) using a 6‐mm or 7‐mm balloon and in 5 of 11 (45%) using an 8‐mm, 9‐mm, or 10‐mm balloon; and moderate/severe edema in 0 of 6 (0%) using a 6‐mm/7‐mm balloon and in 6 of 11 (55%) using an 8‐mm, 9‐mm, or 10‐mm balloon ( P =.048). On POD 7, we found fibroplasia in 5 of 6 (83%) using a 6‐mm or 7‐mm balloon and in 1 of 7 (14%) using an 8‐mm, 9‐mm, or 10‐mm balloon; and moderate/severe fibroplasia in 1 of 6 (17%) using a 6‐mm or 7‐mm balloon and in 6 of 7 (86%) using an 8‐mm, 9‐mm, or 10‐mm balloon ( P =.029). Also on POD7, we found granulation tissue in 0 of 6 (0%) using a 6‐mm or 7‐mm balloon and in 5 of 7 (71%) using an 8‐mm, 9‐mm, or 10‐mm balloon ( P = .021). On POD 30, we found no fibrosis in 0 of 3 (0%) using a 7‐mm balloon, mild fibrosis in 1 of 6 (16.67%), and moderate/severe fibrosis in 5 of 6 (83%) using an 8‐mm or 9‐mm balloon ( P = .048). Also on POD 30, we found the mean subglottic cross‐sectional luminal area was 23.79 mm 2 with a 7‐mm balloon and 29.28 mm 2 with an 8‐mm or 9‐mm balloon ( P = .019). Inflation pressure alone had no correlation with mucosal injury or probability of cricoid fracture. Conclusions: Airway balloon dilation with balloon diameters that exceeded the airway diameter by 2.6 mm was associated with cricoid fractures. All cricoid fractures localized to the anterior cricoid lamina. Balloon diameters larger than the airway diameter by 2.6 mm resulted in a larger subglottic cross‐sectional luminal area on POD 30. Airway balloon dilation with balloon diameters that could generate a cricoid fracture created more mucosal injury on POD 0, 1, and 7 than smaller balloon diameters. The histopathological effects of airway balloon dilation observed on POD 0, 1, and 7 resolved by POD 30. When balloon diameter is kept constant, inflation pressure alone had no correlation with mucosal injury or probability of cricoid fracture. Level of Evidence: NA (animal study). Laryngoscope, 125:S1–S11, 2015